Integration of Perplexity.AI in Poetry Learning in High Schools - Nisa Ashari Putri; Miftakhul Huda (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2026)
This research aims to analyze students' integration of the Perplexity.AI application in poetry learning in high schools. This type of research uses a qualitative approach. The data in this research were 17 students in class X-2 who produced poetry. Subject selection used a saturated sampling technique, namely all students in class X-2 were used as data sources. Subject selection is based on the presence of class X-2 students when collecting poetry results. The data collection techniques used in this research were test technique and questionnaires. The data analysis technique uses thematic analysis. The results of this research, namely the integration of Perplexity.AI in poetry learning in high schools, have proven to increase students' understanding in analyzing poetry based on poetry elements which include theme, diction, rhyme and figure of speech. The form of Perplexity.AI integration in poetry learning in high schools is in the form of Perplexity.AI encouraging students to increase understanding in poetry learning, Perplexity.AI increasing effectiveness and efficiency in poetry learning, Perplexity.AI providing feedback to students in poetry learning, and Perplexity.AI increasing students' learning motivation in poetry learning.